1996
DOI: 10.1145/232807.232815
|View full text |Cite
|
Sign up to set email alerts
|

Strong deviations from randomness in m -sequences based on trinomials

Abstract: The fixed vector of any m-sequence based on a trinomial is explicitly obtained. Local nonrandomness around the fixed vector is analyzed through model-construction and experiments. We conclude that the initial vector near the fixed vector should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…GFSR rejected in an Ising-Model simulation [Ferrenberg, A.M. et al 1992], and a slight modication of trinomials [Fushimi 1990] rejected in [Matsumoto and Kurita 1994]). For these defects, see [Lindholm 1968] [Fredricsson 1975] [Compagner 1991] [Matsumoto and Kurita 1992] [Matsumoto and Kurita 1994] [Matsumoto and Kurita 1996].…”
Section: Number Of Terms In Characteristic Polynomialmentioning
confidence: 99%
“…GFSR rejected in an Ising-Model simulation [Ferrenberg, A.M. et al 1992], and a slight modication of trinomials [Fushimi 1990] rejected in [Matsumoto and Kurita 1994]). For these defects, see [Lindholm 1968] [Fredricsson 1975] [Compagner 1991] [Matsumoto and Kurita 1992] [Matsumoto and Kurita 1994] [Matsumoto and Kurita 1996].…”
Section: Number Of Terms In Characteristic Polynomialmentioning
confidence: 99%
“…In particular, generators for which P (z) is a trinomial or a pentanomial, which have been widely used in the past, do not satisfy this condition and have been shown to fail rather simple statistical tests [Lindholm 1968;Matsumoto and Kurita 1996]. So, as a secondary quality criterion we look at the number of nonzero coefficients in P (z), which we denote by N 1 .…”
Section: Equidistribution and Measures Of Qualitymentioning
confidence: 99%
“…However Lindholm (1968) and Matsumoto and Kurita (1996) have shown that this leads to poor statistical behavior, and argued that there should be near 50% nonzero coefficients in the characteristic polynomial. The MT generators do not satisfy this, but the WELL do.…”
Section: Linear Recurrences Modulo a Large Primementioning
confidence: 99%